2013
DOI: 10.1038/aja.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

An elevated serum miR-141 level in patients with bone-metastatic prostate cancer is correlated with more bone lesions

Abstract: The skeleton is the most common metastatic organ in patients with prostate cancer (PCa). Non-invasive biomarkers that can facilitate the detection and monitoring of bone metastases are highly desirable. We designed this study to assess the expression patterns of serum miR-141 in patients with bone-metastatic PCa. Serum samples were collected to measure the miR-141 level in 56 patients, including six with benign prostatic hyperplasia (BPH), 20 with localized PCa and 30 with bone-metastatic PCa (10 with hormone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 30 publications
0
44
0
2
Order By: Relevance
“…It has been reported that expression patterns of miRNAs can distinguish patients from healthy individuals and the expression characteristics are associated with the developmental lineage of the cancer and of the disease stage [7,8]. Circulating miRNAs have been evaluated as potential noninvasive biomarkers for PCa [4,[9][10][11]. However, the findings are not conclusive.…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…It has been reported that expression patterns of miRNAs can distinguish patients from healthy individuals and the expression characteristics are associated with the developmental lineage of the cancer and of the disease stage [7,8]. Circulating miRNAs have been evaluated as potential noninvasive biomarkers for PCa [4,[9][10][11]. However, the findings are not conclusive.…”
mentioning
confidence: 38%
“…The sensitivity is low and the optimal threshold for biopsy is unclear [3]. On the one hand many patients were over diagnosed due to negative positivity, on the other hand most patients (70 %) are diagnosed at the late stages of PCa and lose the best chances for early treatments [4]. Hence, there is more and more interest in searching for alternative noninvasive biomarkers such as miRNAs.…”
mentioning
confidence: 99%
“…Zhang et al reported that miR-141 can predict tumor progression in prostate cancer (28). Also, high miR-141 plasma level is associated with poor prognosis in colorectal cancer and was proposed as a novel biomarker to find distant metastases (15).…”
Section: Discussionmentioning
confidence: 99%
“…Например, андроген вызывает активацию экспрессии miR-141 в клетках РПЖ in vitro (LNCaP, VCaP) и in vivo [29]. С другой стороны, в ряде независимых исследований повышение уровня этой микроРНК было показано в плазме больных РПЖ [36,37]. С учетом роли экзо-сомальной микроРНК в процессе опухолевой диссе-минации [38], андроген-регулируемые сдвиги профи-ля экспрессии микроРНК клетками РПЖ могут иметь значение в процессе формирования отдаленных мета-стазов [39].…”
Section: том 2 обзорные статьиunclassified